Friedman rule in a model with endogenous growth and cash-in-advance constraint - Firouz Gahvari (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper introduces money into an overlapping generations model with endogenous growth. The model, due to Docquier et al. (2007), exhibits a positive intergenerational externality which precludes its laissez-fair equilibrium to be optimal even if the government can control the level of physical capital and set it to satisfy the modified golden rule. The main message of the paper is that, as long as the modified golden rule is attained, Friedman rule is optimal. The result holds regardless of the ability of the government to internalize the externality and control the level of human capital. Other results include: (i) violation of Friedman rule for a different second-best environment wherein human capital accumulation is controlled but not physical capital accumulation; (ii) existence of a negative relationship between money growth rate and the economy's endogenous growth rate, and (iii) non-uniqueness of Friedman rule.
Keywords: H21; H52; 330; Friedman rule; endogenous growth; investment in human capital; overlapping generations; second best; Geldmengensteuerung; Overlapping Generations; Neue Wachstumstheorie; Cash-in-Advance-Modell; Bildungsinvestition; Second Best; Theorie